Nucleophilic Substitution of Benzyl Halides with in Ammonium Acetate in Presence of Glycerol as Green Solvent - Wolfson, A.; Kimchi, H.; Tavor, D. (Asian Journal of Chemistry, 2010)
Glycerol was employed as a green solvent in the nucleophilic substitution of benzyl halides and ammonium acetate. As a solvent, glycerol facilitated the solubility of both organic molecules and salt and it enabled easy separation of the product.